1982
DOI: 10.1084/jem.155.3.797
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the mechanism of bacterial resistance to complement-mediated killing. I. Terminal complement components are deposited and released from salmonella minnesota S218 without causing bacterial death

Abstract: It has been recognized since 1895 (1) that some gram-negative bacteria are sensitive to the lytic action of fresh serum, whereas others are highly serum resistant. In general, serum-resistant organisms are more pathogenic than serum-sensitive bacteria in animal models of infection, and serum-resistant organisms are more commonly isolated from the bloodstream of patients with gram-negative bacteremia (2). In attempts to define the basis of this important virulence factor, characteristics of the outer membrane o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
114
1

Year Published

1982
1982
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(119 citation statements)
references
References 20 publications
4
114
1
Order By: Relevance
“…These findings suggest that differences exist between the susceptibility of erythrocytes and Salmonella to the lytic/ bactericidal effects of mouse complement, with Salmonella being more resistant than erythrocytes. Complement that does not insert into the Salmonella outer membrane can be shed from the surface of S. Minnesota (26,27), and various molecules on the Salmonella surface, including those encoded by rck (28), traT (29), and pgtE (30), confer some degree of resistance to complement-mediated killing.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that differences exist between the susceptibility of erythrocytes and Salmonella to the lytic/ bactericidal effects of mouse complement, with Salmonella being more resistant than erythrocytes. Complement that does not insert into the Salmonella outer membrane can be shed from the surface of S. Minnesota (26,27), and various molecules on the Salmonella surface, including those encoded by rck (28), traT (29), and pgtE (30), confer some degree of resistance to complement-mediated killing.…”
Section: Discussionmentioning
confidence: 99%
“…In the 1980s, Joiner showed that when complement membrane attack complex forms on lipopolysaccharide on the surface of salmonellae, it can be cleaved off (37) and thus fail to insert into the bacterial outer membrane (38). In addition, rck is associated with abnormal polymerization of C9 in the membrane attack complex (39).…”
Section: Figure 10mentioning
confidence: 99%
“…Long-chain LPS has been shown to confer resistance by promoting the deposition of complement components at a distance from the outer membrane, thus allowing the MAC to be shed from the bacterial surface without disrupting membrane integrity (3,4). The PhoPPhoQ-regulated gene pagC has been shown to confer resistance when expressed in both E. coli and S. enterica Choleraesuis by a currently uncharacterized mechanism (5).…”
mentioning
confidence: 99%